A Systematic Literature Review of Benchmarking Implementation in various Industries - Yulio Agefa Purmala; Fransisca Debora (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2021)
This paper aims to explore benchmarking in various industries beyond Indonesia to find the gap between each industry and what makes it different from Indonesia. Benchmarking is recognized as an essential instrument for continuous quality enhancement. In this paper, the author has reviewed 60 articles distributed from 2015 to 2020 in a variety of journal research and journal review. Systematic literature reviews are the approaches used in this study since a precise, consistent, and clear methodology, with a variety of steps, guarantees sufficient rigor and clarity in the literature review process. Authors have a review in multi-perspective to help researchers, academics, and practitioners more deeply understand and take a closer look at the growth, development, and applicability of this technique. Authors have classification the various paper-based on goals and scope of achievement from benchmarking applicable. In Addition, this paper also needs to find a better solution from each gap of benchmarking in the pandemic situation with the industry 4.0 approach